Comparison of the functional properties between coconut residue flour and protein enriched coconut residue flour - Malubay, Nevien M.; De Leon, Sonia Y. (1993.)
Theprotein enriched coconut residue flour (PECRF) and coconut residue flour (CRF) were evaluated according to their functional properties using all-purpose wheat flour (APF) as reference. The properties tested were divided into hydration properties which include solubility at different pH levels and at high temperature and water absorption: surface-active properties composed of emulsion formation and emulsion stability, fat absorption, foamability and foam stability; and rheologial properties consisting of gelation, viscosity, dough and film formation. CRF had higher solubility at various pH levels, higher water absorption, better emulsion formation and higher fat absorption than PECRF. ECRF on the other hand, had a higher solubility at high temperature, higher emulsion stability both at high and low temperatures, and was more viscous than CRF. Both flours had no foaming, gelation, dough and film formation abilities.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Enriched foods; Coconut residue flour